2019
DOI: 10.1352/1944-7558-124.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of Later Expressive Language in Boys With Fragile X Syndrome

Abstract: The predictive ability of early consonant inventory and intentional communication on later expressive language was examined in 36 boys with fragile X syndrome (FXS). Autism symptom severity was included as a potential moderator. Participants were visited in their homes twice over a 6-year period, and mother-child interactions were videotaped, coded, and transcribed behavior by behavior. Consonant inventory and concurrent autism symptom severity were predictive of later number of different words, as was the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Recent research has found that increased autistic symptomatology is generally associated with greater communication delay in FXS, and this is in agreement with previous research (Abbeduto and Hagerman, 1997;Abbeduto et al, 2007;Finestack et al, 2009;Fielding-Gebhardt and Warren, 2019;Mattie and Hamrick, 2022). The impact of autistic symptomatology has been demonstrated in gestures, gaze shift, and initiation of joint attention (Flenthrope and Brady, 2010;Hahn et al, 2016Hahn et al, , 2017Brewe et al, 2018;Rague et al, 2018;Hughes et al, 2019).…”
Section: Related Factorssupporting
confidence: 89%
“…Recent research has found that increased autistic symptomatology is generally associated with greater communication delay in FXS, and this is in agreement with previous research (Abbeduto and Hagerman, 1997;Abbeduto et al, 2007;Finestack et al, 2009;Fielding-Gebhardt and Warren, 2019;Mattie and Hamrick, 2022). The impact of autistic symptomatology has been demonstrated in gestures, gaze shift, and initiation of joint attention (Flenthrope and Brady, 2010;Hahn et al, 2016Hahn et al, , 2017Brewe et al, 2018;Rague et al, 2018;Hughes et al, 2019).…”
Section: Related Factorssupporting
confidence: 89%
“… 8 Early use of consonants during babbling and intentional communication, including the use of gestures, is predictive of later expressive language. 9 By the time of preschool, though, children with FXS have the ability to repair a breakdown in communication (i.e., when there is a miscommunication with a conversational partner), indicating well-developed language and social skills. In addition, maternal language plays a role in language development.…”
Section: Resultsmentioning
confidence: 99%
“…Children's developmental stages are not reached simultaneously. Some children do not reach developmental milestones as fast as their peers do, or they may have only recently caught up to the developmental stage of their peers (Fielding‐Gebhardt & Warren, 2019). The entire developmental stage of a child may experience delays in one area.…”
Section: Introductionmentioning
confidence: 99%